The Influence of Work Culture, Motivation, and Leadership on Employee Performance at PT. Herfinta Form & Plantation - Farah Miranda Nasution; Yohny Anwar; Emi Wakhyuni (Utan Kayu Publishing, 2025)
This study aims to determine and analyze the positive and significant influence of work culture, motivation, and leadership on employee performance at PT Herfinta Farm Plantation. This quantitative study used a questionnaire as a data collection instrument. The sample used in this study was saturated, consisting of all 64 employees of PT Herfinta Farm Plantation. Data analysis used multiple linear regression with the Statistical Package for the Social Sciences (SPSS) version 24.0. The results obtained indicate that testing Hypothesis 1 (one) shows a positive and partially significant influence between work culture and employee performance at PT Herfinta Farm Plantation. Testing Hypothesis 2 (two) shows a positive and partially significant influence between motivation and employee performance at PT Herfinta Farm Plantation. Testing Hypothesis 3 (three) shows a positive and partially significant influence between leadership and employee performance at PT Herfinta Farm Plantation. Testing Hypothesis 4 (four) shows a simultaneous positive and significant influence between work culture, motivation, and leadership on employee performance at PT Herfinta Farm Plantation